HUBUNGAN KONSEP DIRI DENGAN PENERIMAAN DIRI DAN KEMANDIRIAN PADA LANSIA : LITERATUR REVIEW - Dya Sustrami (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2021)
Background : Elderly is someone who is entering the age above 60 years. Elderly can be characterized by physical changes including thin and gray hair, toothless teeth, decreased hearing, decreased vision and wrinkled or sagging skin. This study aims to determine the relationship between self-concept and self-acceptance and independence in the elderly. Method : This research design is a study using the literature method or literature review. The study population was the elderly aged over 60 years. Search for journal articles using the keywords English and Indonesian as well as in combination with the boolean operator (AND, OR NOT or AND NOT). A total of 100 journals were obtained, then classification according to the inclusion criteria were 11 journals. Results : The findings that have been analyzed by researchers as a whole are formulated that